Swasth Saarthi Abhiyan for public transport drivers, filling fuel at Indraprastha gas limited stations in Delhi and National Capital Region - Vaghela, Joyce Felicia; Kumar, Amod; Sharma, Amita; Gupta, Vinita; Bannerjee, Sayantan; Das, Harveen (International Journal Of Community Medicine And Public Health, 2019)
Background: A public transport driver (Saarthi) if sick thinks twice before taking a day off. The community health department (CHD) of a tertiary care hospital started a ‘Swasth Saarthi (healthy drivers) Abhiyaan’ (SSA) for the public transport drivers (PTDs) for one year. The objectives of the study were to conduct 220 health check-up camps at selected compressed natural gas (CNG) stations in Delhi and National Capital Region; to improve health awareness and early detection of diseases in drivers and getting treated at base hospital. Methods: A cross-sectional study carried out from 15th March 2017 to 14th March 2018 at 36 Indraprastha Gas Limited (IGL) stations for all public transport drivers coming to IGL stations. Health camps conducted were - general health camp at IGL stations, NCD camps at community health department and clinical camps at the base hospital. Results: A total of 408 camps were held in which 14,945 drivers came for health check-up. The PTDs with Eye problems 5981 (40%), over-weight 5315 (35.56%), tobacco/gutka chewing 4687 (31.36%), drinking 3734 (24.98%), smoking 3616 (24.20%), obesity 1655 (11%), hypertension 1433 (9.59%) and diabetes 1057 (7.07%). Health awareness was improved through health education. Surgeries for cataract 20/155 and sleep apnoea 4/122, and de-addiction drugs for 15 drivers of ‘addiction’ were started at base hospital. Conclusions: The health check-up camps under SSA revealed that a large number of public transport drivers are at risk of various health related disorders. Innovative programme like ours is good to reduce “Treatment Gap” and is a step towards achieving Universal “Health for All”.